Harmonisation du droit européen des contrats: enjeux et défis - Atmani, Bilal (Revue Académique de la Recherche Juridique, 2015)
L’harmonisation du droit des contrats demeure un objectif à atteindre pour la commission européenne qui a multiplié les appels au rapprochement des règles du droit des contrats au niveau interne tout en respectant la souveraineté des Etats membres de l’union. La commission européenne a réaffirmé, à l’occasion de l’adoption de deux résolutions adoptées en date des 23 mars 2006 et 06 septembre 2006, sa conviction qu’un marché intérieur uniforme ne peut être pleinement opérationnel sans de nouveaux efforts d’harmonisation du droit civil. Ma contribution vise à étudier la politique européenne en matière d’harmonisation du droit des contrats et mettre en lumière le constat de cette politique.
Keywords: Contrats; Droit des contrats; Droit européen; Harmonisation; Principes fondamentaux; Sécurité juridique

Le régime juridique de la rémunération des dirigeants sociaux en droit OHADA - Nevry, Roger (Revue juridique de l'Océan Indien, 2015)
Keywords: Administrateur; Administration; Assemblée générale; Conseil d'administration; Contrat de travail; Direction; Dirigeant social; Droit OHADA; Droit des affaires; Droit des sociétés commerciales; Gérant; Jetos de présence; Président; Remboursement; Rémunération; S.A.; SARL; Société à responsabilité limitée; Sociétés Anonyme; sociétés en nom collectif

La codification du droit de la famille : une harmonisation aléatoire du droit algérie - Filali, Ali (Annales de l’Université d’Alger, 2015)
Le recouvrement de l’Indépendance nationale devait être accompagné par un retour à la culture et aux valeurs authentiques de la société algérienne. Ainsi est apparue la nécessité d’élaborer un droit algérien devant se substituer à la législation coloniale. Néanmoins, le contexte dans lequel devait être entreprise cette œuvre était très complexe, compte tenu de l’influence de plusieurs systèmes juridiques. Le problème s’est posé spécialement pour le droit de la famille, dont les règles de fond inspirées exclusivement par la chari’a devaient faire l’objet d’une codification de sorte à faire partie intégrante du corpus juridique algérien. Cette démarche a soulevé, toutefois, beaucoup de difficulté, car le procédé de codification emprunté au droit occidental est incompatible avec la nature même des règles de la chari’a
Keywords: Acculturation juridique; Chari’a; Code de la famille; Codification; Cohabitation; Concept juridique; Fiqh; Harmonisation; Système juridique

Une approche régionale de l’harmonisation du droit des affaires : l’exemple de l’OHADA - Haddoum, Kamel (Annales de l’université d’Alger, 2015)
Pour faire face au phénomène de la mondialisation du marché international des affaires et des défis qu’il met en jeu, le développement économique semble s’orienter de plus en plus vers une approche régionale afin de mieux défendre les intérêts nationaux pourtant souvent contradictoires. En effet, la mondialisation de l’économie exige la mondialisation du droit., l’un des exemples le plus illustratif, nous viens de l’Afrique, qui a privilégié l’intégration régionale par le droit des affaires, à travers la création de l’Organisation de l’OHADA qui devait permettre à une partie de l’Afrique de mieux s’intégrer à l’économie mondiale, de faciliter les échanges entre les Etats parties, d’attirer les investisseurs étrangers, et de mettre fin à l’insécurité juridique. Selon les initiateurs du traité OHADA, l’intégration économique qui est une condition sine qua non du développement de la région, ne peut réussir, qu’à travers la mise en place d’une harmonisation du droit des affaires. Le fonctionnement de L’OHADA s’appuie sur un certain nombre d’organes et sur l’élaboration de plusieurs Actes Uniformes touchant au domaine du Droit des Affaires constituant ainsi le droit dérivé. Néanmoins face à un environnement économique et juridique en constante évolution, l’OHADA était dans l’obligation de mener des réformes d’ordre institutionnel et normatif.
Keywords: Actes Uniformes; Afrique; Arbitrage africain; Droit des affaires; Economie Africaine; Harmonisation juridique; OHADA; Régionalisation

Une approche régionale de l’harmonisation du droit des affaires : l’exemple de l'OHADA - Haddoum, Kamel (Annales de l’Université d’Alger, 2015)
Pour faire face au phénomène de la mondialisation du marché international des affaires et des défis qu’il met en jeu, le développement économique semble s’orienter de plus en plus vers une approche régionale afin de mieux défendre les intérêts nationaux pourtant souvent contradictoires. En effet, la mondialisation de l’économie exige la mondialisation du droit., l’un des exemples le plus illustratif, nous viens de l’Afrique, qui a privilégié l’intégration régionale par le droit des affaires, à travers la création de l’Organisation de l’OHADA qui devait permettre à une partie de l’Afrique de mieux s’intégrer à l’économie mondiale, de faciliter les échanges entre les Etats parties, d’attirer les investisseurs étrangers, et de mettre fin à l’insécurité juridique. Selon les initiateurs du traité OHADA, l’intégration économique qui est une condition sine qua non du développement de la région, ne peut réussir, qu’à travers la mise en place d’une harmonisation du droit des affaires. Le fonctionnement de L’OHADA s’appuie sur un certain nombre d’organes et sur l’élaboration de plusieurs Actes Uniformes touchant au domaine du Droit des Affaires constituant ainsi le droit dérivé. Néanmoins face à un environnement économique et juridique en constante évolution, l’OHADA était dans l’obligation de mener des réformes d’ordre institutionnel et normatif.

Online dispute resolution: The future of justice - Mania, Karolina (International Comparative Jurisprudence, 2015)
The purpose of this study is to present the main facets of online dispute resolution, including a definition of the term, the types of resolution available, and the most recent legal regulations in this area. The article is an in-depth study of this field, discussing online mediation and electronic arbitration, their uses and their relationships with e-commerce. The strengths and weaknesses of online dispute resolution are identified and used to help formulate de lege ferenda stipulations. The paper is divided into three parts. Part I looks at preliminary aspects of online dispute resolution (ODR), including a definition of the term and an examination of its phases of development, implementation examples and the relationship between ODR and technology. Part II is devoted to examining the two most frequent forms of ODR: online mediation and electronic arbitration. Part III is an analysis of consumer disputes arising from commercial transactions made using electronic communications. As an example of the implementation of ODR, the author emphasises the importance of new European regulations on that and alternative dispute resolution (ADR): Directive 2013/11/EU of the European Parliament and of the Council of 21 May 2013 on alternative dispute resolution for consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC (Directive on consumer ADR), and Regulation (EU) No 524/2013 of the European Parliament and of the Council of 21 May 2013 on online dispute resolution for consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC (Regulation on consumer ODR).
Keywords: ADR; Alternative dispute resolution; Consumer dispute; E-commerce; Electronic arbitration; ODR; Online Dispute Resolution; Online mediation

L’accès aux fonctions de dirigeant social en droit communautaire africain des affaires - Talfi, I. Bachir (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2015)
Le droit OHADA pose, en matière de sociétés commerciales, le droit commun de l’accès aux fonctions de dirigeant de société. Cependant, en dehors du droit OHADA, le droit communautaire sectoriel de l’UEMOA, de la Cima et du CREPMF contiennent également des règles spéciales en matière de droit des sociétés, notamment en ce qui concerne l’accès aux fonctions de dirigeant de société. Ces règles, bien qu’évoluant dans le contexte de l’harmonisation et de l’uniformisation du droit ne sont pas uniformes. De telle sorte que l’accès aux fonctions de dirigeant de société est sujet à plusieurs règles éparpillées et sans lien entre elles. Cette étude vise à montrer que le contexte de l’uniformisation des règles en droit des affaires doit conduire à une uniformisation des règles en passant par la rationalisation de l’intervention du législateur communautaire de droit des affaires. Elle vise également à démontrer que l’accès aux fonctions de dirigeant de société se présente sous une double facette : celle d’une apparente ouverture de l’accès et de réelles restrictions. Ces règles restrictives édictées dans le but de faire la police de l’accès aux fonctions de dirigeant tournant autour d’une dimension éthique que le législateur veut insuffler sans y parvenir réellement.

La fondamentalisation du droit privé - Marguénaud, Jean-Pierre (Revue de droit d'Assas, 2015)

The Modern Travelling Merchant: Mobile Communication in International Contract Law - Schroeter, Ulrich G. (Journal of Law, Society and Development, 2015)
The use of mobile communication devices such as mobile phones, smartphones, tablet computers or notebooks with access to the internet has become an everyday phenomenon in today's business world. However, whenever mobile communications are used for the purposes of contract formation, that is, the mobile dispatch of offers or acceptances, the mobility of the communicating parties raises important difficulties for the application of traditional legal rules: The fact that messages transmitted via phone, email or SMS can be dispatched and received Â at virtually any Â place on Â earth challenges the categories of private international law and international contract law, which are based on the (unspoken) assumption that parties communicate from their home country. The existing legal framework for cross-border contracts therefore hardly takes into account the possibility that parties may move across borders, and that the place of their communications may accordingly vary.The present article addresses the legal difficulties and uncertainties that crossÂ border Â mobile communication Â raises under international rules of law. It elaborates on the traditional role of the site of communication in this context before scrutinising how 'mobility friendly' the provisions Â of the relevant Â conventions Â developed Â by the United Nations, the Hague Conference for Private International Law and other organisations Â are. In doing Â so, Â it critically Â discusses Â in particular article 10(3) of the UN Electronic Communications Convention of 2005, the most recent attempt at regulating mobile communications. Finally, it identifies a number of problems that have hitherto been overlooked (as notably the interaction of article 10(3) of the UN Electronic Communications Convention with traditional private international law rules on the formal validity of contracts) and proposes appropriate solutions.
Keywords: Conflict of laws; Contract law; Electronic communication; Electronic contract formation; Mobile communication; Place of contracting; UN Electronic Communications Convention; m-commerce

Policy Options for Promoting Foreign Direct Investment in the Least Developed Countries - Sauvant, Karl P.; Mallampally, Padma (Transnational Corporations Review, 2015)
Foreign direct investment (FDI) plays an important role in the world economy and has the potential to contribute towards accelerating the process of economic growth and sustainable development in the least developed countries (LDCs). The paper provides a brief overview of recent trends and patterns in FDI flows to the LDCs, and then takes stock of the policies, programmes and measures pursued by host and home countries and by international organizations to stimulate FDI flows to LDCs and increase their benefits for these countries. It then lays out a number of policy proposals on how flows to LDCs, and the benefits associated with them, can be enhanced. Finally, it outlines some options for international action to strengthen such efforts – proposals and options that are also relevant to other developing countries.
Keywords: Development; Foreign direct investment; Least Developed Countries; policy options

BRICS and Sub-Saharan Africa Trade Interdependence and Peace: Evidence Based on Revealed Comparative Advantages - Beyene, Hailay Gebretinsae (Journal of Law, Society and Development, 2015)
This study examined economic integration through trade between BRIGS (Brazil, Russia, India, China and South Africa) countries and sub-Saharan Africa. The study examines the comparative advantages of the two economic blocks with respect to the exportation of merchandise (food, agricultural raw materials, fuels, ores and metals, and manufactures). The findings of this study reveal the actual status of these two regions as economic partners in each of the five subsectors of merchandise exports.The Â trend Â shows Â that, Â with Â the Â exception Â of Â manufactures Â exports, the competitiveness of all subsectors of the merchandise Â exports ofÂ BRIGS is characterised by a Â declining Â trend. Â BRIGS has Â a Â comparativeÂ advantage in the world in the exportation of manufactures and fuels, and comparative disadvantage in the export of food, agricultural raw materials, and ores and metals. Â Interestingly, manufactures are Â continuously Â and consistently Â in a steadily rising trend. This is evidence that BRIGS's structural transformation towards higher valued-added commodities is proceeding well, which means that policy makers should be considering ways of enhancing it further.In the case of sub-Saharan Africa,Â with the exception of manufactures exports, it is found to have comparative advantages in all merchandise exports. Sub- Saharan Africaâ€™s competitive advantage is the highest in the exportation of ores and metals, followed by fuels, agricultural raw materials and food. Sub-Saharan Africa has a comparative disadvantage in the export of manufactures throughout the period considered in this study. This implies that the prospects of structural transformation to downstream of the higher value-added commodities export part of the supply chain are good: the slow pace of transformation towards higher value-added goods should therefore be demanding the attention of policy makers. The study has revealed that sub-Saharan Africa is more competitive than BRICS in the exportation of ores and metals, fuel, agricultural raw materials and food. On the other hand, BRICS is more competitive than sub-Saharan Africa in the export of manufactures.The study has also revealed that significant economic integration can be sustained Â between Â BRICS Â and Â sub-Saharan Â Africa Â in Â the Â exportation Â of all merchandise subsectors. Specifically, sub-Saharan Africa is a potential destination market for BRICSâ€™s exports of manufactures. Conversely, BRICS is also a potential destination market for sub-Saharan Africaâ€™s exports of ores and metals, fuel, agricultural raw materials and food.Economic integration between BRICS and sub-Saharan Africa favourably influences peace and stability in the regions. Sustaining peace and stability in these regions also favourably influences the wellbeing of the communities.
Keywords: BRICS; Economic integration; Sub-Saharan Africa; merchandise exportation; peace and stability; revealed comparative advantage; structural transformation

CISG and Regional Sales Law: Friends or Foes? - Coetzee, Juana (Journal of Law, Society and Development, 2015)
Economic co-operation and integration brings with it a need to harmonise mechanisms for the regulation of international trade, not only at a public-law level between states but also at a private-law level between traders inter partes. It is often forgotten that differences in the substantive law applicable to a contract function as a non-tariff barrier to trade. Because international trade facilitates economic development, the focus in this article is on the harmonisation of sales laws. Traditionally, private law harmonisation has been conducted by international private or inter-state organisations that specialise in the harmonising of law at a global level. Today, private organisations and groups devoted to harmonising business laws, as well as regional economic integration organisations, are also pursuing legal harmonisation. Global, regional and domestic laws now all exist in the same area of the law, which can give rise to duplication of efforts and problems with the co-existence of global and regional sales law. This article will discuss these issues with reference to the United Nations Convention on Contracts for the International Sale of Goods (CISG) and selected regional laws in considering whether regional harmonisation can act as a stepping stone towards increased harmonisation at a global level or whether it is to be viewed as a threat to global integration and harmonisation.
Keywords: CESL; CISG; Global harmonisation; Harmonisation of sales laws; OHADA; PACL; SADC; regional harmonisation

Regional Labour Standards in the SADC: Is It Possible, Given the EU Experience? - Smit, Paul (Journal of Law, Society and Development, 2015)
Globalisation and the increasing movement of capital and labour across international borders, with the exception of migrant workers who are facing major obstacles due to immigration laws, are creating a situation where laws in general and labour laws in particular are acquiring an international character. International bodies such as the United Nations, the International Labour Organisation and the European Union have adopted various international norms and standards to which most countries have agreed and which have established minimum international standards for basic universal human rights and worker rights. The Southern African Development Community is a transnational organisation that has also adopted certain basic norms and standards in its Treaty, Charter on Fundamental Social Rights and various protocols that are applicable to all citizens within the Community. In this contribution, the concept of transnational labour relations is considered. The different international approaches towards transnational labour relations are evaluated, as is the manner in which the European Union approached the integration of regional labour standards. The author seeks to establish what the Southern African Development Community can learn from the European Union’s experience and in what way a transnational labour relations system or regional labour standards regime for the Southern African Development Community can be established.
Keywords: Regional integration; Transnational labour relations (TNLR); international law; labour rights; regional labour standards; social rights

L’adhésion de la République Démocratique du Congo à l'OHADA et son apport mitigé sur la capacité juridique de la femme mariée en matière professionnelle - Ngimbi, Jean-Michel Kumbu ki; Lumingu, Yves-Junior Manzanza (Recht in Afrika, 2015)
In Congolese law, the legal capacity of the married women is subjected to certain limitations. These restrictions include, notably, the exercise of professional activities for which marital authorization is a legal requirement. This is why some consider the adherence of the Democratic Republic of the Congo (DRC) to OHADA as an opportunity in favour of the married woman, claiming that all provisions of domestic law clinging on the legal incapacity of the latter are automatically repealed because supposedly contrary to the uniform Acts, and in this case the uniform Act relating to general commercial law (AUDCG). This paper attempts to meticulously analyse the alleged contribution resulting from the OHADA law and manages to demonstrate that the status of the married woman in professional matters from the standpoint of OHADA has indeed not changed. A first step in that direction could have been for the AUDCG to explicitly recognize the married woman's ability to freely engage into trade. Unfortunately the corresponding provision only deals with the status of the spouse of the trader, thus leaving the issue of legal capacity of the married woman on commercial matters to the national laws of each of the member states. Even though some progress in commercial law may be recognized, this could not cover other professions governed by national legislation and that are, consequently, out of the scope of the Uniform Acts. Hence, a genuine reform in order to release the married women from the marital authorization regime is a necessity.

Cooperative Movements in the Western Highlands of Cameroon - Jiotsa, Albert; Okia, Timothy Musima; Yambene, Henri (Revue de géographie alpine, 2015)
Cooperative societies in the Western Highlands (West and North West regions) of Cameroon is an age old institution which started with the arrival of the European colonialists towards the end of the nineteenth century. The fertile soils of this region favors agricultural activities thereby giving rise to many cooperatives in the region. The cooperative societies that have been developed in these areas are the type found in sub Saharan Africa which has stood the test of time more than half a century whereby the other cooperatives elsewhere in the same country have failed. The question this article is about to provide answers is to what has made these cooperatives in the Western Highlands of Cameroon able to stand the test of time when others are quitting the scene. To come out with this scientific article we have implored the active participatory research methodology. The analysis shows that these cooperatives since their creation have been imploring certain innovative measures to make them adapt to the many constraints in their sector.
Number: 103-1
Keywords: Cameroon; adaptation strategies; constraints; cooperative movements; highlands

Le déclin de exorbitance du droit administratif sénégalais sous l’effet du droit communautaire - Kebe, Abdou Aziz Daba (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2015)
I) L’indifférence du statut de la puissance publique dans l’applicabilité du droit communautaire A) La prépondérance du critère matériel d’application du droit communautaire 1) Le critère de commercialité dans la législation OHADA 2) L’entreprise dans la législation UEMOA B) Le maintien exceptionnel du critère organique pour l’application du droit communautaire 1) Une immunité d’exécution conférée aux organismes publics 2) L’élargissement par la CCJA du spectre des personnes bénéficiaires de l’immunité d’exécution II) Une restriction du champ d’application du droit administratif A) L’expansion du doit communautaire dans les secteurs d’activité de la puissance publique 1) La soumission du service public aux règles concurrentielles 2) L’immixtion du droit privé dans le domaine des contrats administratifs B) Le contournement du juge de l’administration 1) Le droit pour les personnes publiques de recourir à l’arbitrage 2) La renonciation par l’administration à son privilège de juridiction Conclusion

Plaidoyer pour le développement du cautionnement mutuel dans la zone OHADA - Zio, Moussa (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2015)

Formation du contrat électronique : l’acceptation entre mutations et orthodoxie - Kablan, Serge; Onana Onguene, Édouard (Revue de droit d’Ottawa, 2015)
La doctrine a souvent débattu sur la nature du droit du cyberespace, c’est-à-dire le type de règles qui doivent encadrer les transactions électroniques. La formation du contrat électronique B2B et B2C permet d’aborder ce débat sous un angle pratique, qui met le législateur devant deux options connues : l’une, qui encourage l’élaboration de règles typiques, compte tenu d’une spécificité présumée de ces contrats ; l’autre, tendant à privilégier le droit existant, éventuellement adapté. Le formalisme issu des récentes productions législatives, notamment en droit de la cyberconsommation, réaffirme le rôle essentiel du consentement dans la formation du contrat, avec la reconduction automatique des opérations traditionnelles de l’offre et de l’acceptation. Mais dans le cyberespace, la manière d’exprimer ces deux opérations bénéficie de balises pratiques plus ou moins précises, peut-être pour éviter que des règles impératives en la matière ne vieillissent trop rapidement à cause du contexte technologique en perpétuelle transformation. Or, cette hésitation, peut-être ce choix, a fait émerger plusieurs modalités d’expression de l’acceptation dont la validité n’est pas acquise de façon mécanique, mais demeure fréquemment suspendue à l’appréciation des juges. Mais en examinant les motifs progressivement développés par les tribunaux en common law et en droit civil, de même qu’en doctrine, les auteurs décelent une constante, un critère invariable dans l’appréciation du rituel de l’acceptation en ligne. Cette analyse dépasse ainsi ces techniques apparues des usages, c’est-à-dire le « Box-Top », « Shrink-Wrap », « Browse-Wrap », « Click- Wrap », « Hybrid Click-Wrap », « Hyperwrap », et tente de définir et de circonscrire cette valeur, ce critère qui ins pire un retour aux fondements traditionnels du droit des contrats. Nous proposons, enfin, de recourir à des pictogrammes pour réaliser la mise en oeuvre de ce critère.

Law and Development in West and Central Africa OHADA - Winship, Peter (SMU Dedman School of Law Legal Studies Research Paper, 2015)
This seminar paper considers whether OHADA - an experiment in unifying business law in African countries - has been a success. Following a prologue that explains the origins of the paper, the first part of the paper sets out basic information about the Organisation pour l’Harmonisation du Droit des Affaires en Afrique (“Organization for the Harmonization of Business Law in Africa,” known by the acronym OHADA). This part is followed by a review of law and development literature to assess the value of this literature for an evaluation of the success (or not) of OHADA. A third part then focuses on one specific uniform law, the law of secured transactions. The paper concludes that notwithstanding challenges the OHADA institutions exist and have produced uniform business laws for the formal business sector. Whether OHADA has been the cause of increased investment and trade requires studies that have not been carried out.
Keywords: African law; Secured transactions; commercial law; law and development; law reform; unification of law

Toward an Elaboration of a More Pluralistic Legal Landscape for Developing West African Countries: Organization for the Harmonization of Business Law in Africa (OHADA) and Law and Development - Hiez, David; Menétrey, Séverine (The Law and Development Review, 2015)
In Europe and especially in France, the African business law landscape, as well as the legal discourse, for developing West African countries is almost exclusively dedicated to OHADA, the Organization for the Harmonization of Business Law in Africa, created in 1993. While economic development in the Member States is the obvious underlying reason for the modernization and unification of African business law, the exact nature of such development remains uncertain, as does the manner in which a such result can or will be achieved. OHADA’s Uniform Acts are, with some minor exceptions, a carbon copy of French business law. The only goal is to increase international investment, which, in turn, is expected to generate economic development, but all without taking any notice of equality or social justice issues. That, without a doubt, is the reason why OHADA is constantly criticized as a law that benefits foreign investors, while remaining ineffective, even illusory, for local traders. To go beyond the criticism, the authors have decided to focus on the relationship between law and the informal sector and to draw lines between formal and informal rules in the business sector.
Keywords: Informal rules informal sector; OHADA (Harmonized Business Law in Africa); informal rules; informal sector

Titrisation, Afrique : le cas du Maroc et de l’Union Economique et Monétaire Ouest Africaine (UEMOA) » - Abbour, Abdelali (Revue Interdisciplinaire, 2015)
Sous l’effet de des phénomènes de mutations dans les sociétés, on a assiste à une floraison de nouvelles activités ou de nouveaux instruments financiers. Concomitamment à cette prolifération de nouveaux produits ou techniques financières ; il est tout aussi apparu nécessaire d’adapter le secteur bancaire et financier de certains pays africains aux évolutions liées principalement aux nouveaux besoins de financement de leur économie nationale, à l’ouverture sur l’extérieur et aux opérations internationales et à l’introduction de l’innovation financière et technologique… Ceci est le cas pour le Maroc.
Number: 1
Keywords: Afrique; Maroc; Titrisation; UEMOA; Union Economique et Monétaire Ouest Africaine

La protection de la caution illettrée - Akpoue, Brou (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2015)
La réforme du droit des sûretés en vue de le rendre plus attractif n’a pas suffisamment pris en compte la sécurité juridique de la caution illettrée. Elle a tout simplement confirmé la solution reprise au droit de certains pays de l’OHADA tels que le Sénégal, le Mali et la Guinée-Conakry. Pourtant, il apparaît possible de renforcer la protection de la caution en question. La révision des règles qui régissent la situation de celle-ci s’imposent.
Keywords: Cautionnement; Securities; Sûreté

La protection des créanciers du vendeur de fonds de commerce dans l'espace OHADA - Balla Kalto Loutou, Amina (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2015)
La protection des créanciers du vendeur de fonds de commerce s’inscrit dans un contexte global de la garantie de sécurité juridique et judiciaire que le législateur tente d’offrir aux investisseurs dans l'espace OHADA. Il vise à réaliser cet objectif par l’élaboration d’une règlementation appropriée en instituant des mesures de publicité ou d’exécution forcée de leurs droits de créance que le juge OHADA (gardien de la légalité et garant de la protection des droits individuels des justiciables) tente d’appliquer de manière effective. Business vendor’s creditor’s protection is in line with the general pattern of legal and judicial security guarantee that the legislator tries to offer to the investors in OHADA’s legislation space. To achieve its aim, the legislator draws up investors’ protection centered on regulation by taking steps consisting of advertisement measures or forced execution of investors’ claims and entrusts the guardian of legality and guarantor of justiciables’ individual rights protection, OHADA’s judge with the mission to check if these protective norms are efficient.
Keywords: Action paulienne; Droit de surenchère; Déchéance du terme; Exécution forcée; Fonds de commerce; Opposition au paiement; Publicité; Sécurité judiciaire; Sécurité juridique

Les pouvoirs d’office du juge des procédures collectives de l'Organisation pour l'Harmonisation en Afrique du Droit des Affaires (OHADA) et les principes cardinaux du procès - Biboum Bikay, François (Juridical Tribune - Review of Comparative and International Law, 2015)
The law of collective proceedings for clearing off depts which replaces the former bankruptcy law pursues an economic objective the reason why it carries certain exceptions to the common procedure law. As such, the judge of collective proceedings has powers of initiative in the institution and conduct of the trial. He can thus of his own initiative open the collective proceeding. The aim of this study is to confront the judge's office powers with the cardinal principles of the trial. The expected result should help verify the compatibility of those powers with the requirements of a fair trial. A hypothesis emerges that automatically powers that deviate somewhat to the cardinal principles of the trial, are justified by the aim of safeguarding collective interests pursued by the insolvency judge.

Revue de la jurisprudence 2014 en droit des entreprises - Bouchard, Charlaine (Revue du notariat, 2015)

La prise en compte du statut d'époux par le droit des affaires de l'Organisation pour l'Harmonisation en Afrique du Droit des Affaires (OHADA) - Djombi, André Desmonds Eyango (Juridical Tribune - Review of Comparative and International Law, 2015)
Taking into account the status of spouses by business law of the Organization for the Harmonization of African Business Law (OHADA) is referring to general commercial law and company law. The OHADA legislator values the status of spouses devoting equality between spouses, through the possibility for them to be able to be involved in low risk companies; the recognition of the de facto company between them and the right granted to each power, under the same conditions, benefit from the commercial lease originally attached to privileges. The consideration that the OHADA law grants the quality of husband appears in heritage protection thereof, insofar as it puts it away in case of depletion bad deal made by one of them . This is why the prohibition for spouses to be involved in the unlimited risk firms and the requirement of a separate trade as a condition for the spouse of the trader can also acquire the same status. But the heritage protection system spouse taken from the OHADA business law is supplemented by certain mechanisms of civil law, including matrimonial property regimes, although not all have the same efficiency. Indeed, among the two groups of matrimonial property regimes are known as separation schemes and those of the community property, only the first effectively protect the couple's assets. This objective likely was not assigned to the second from the design. These look more forward the merger of most of the assets of the couple without the slightest idea of calculation.
Keywords: Business law; OHADA; status of married people.; trading companies

La nullité en droit des sociétés coopératives OHADA au regard du droit canadien des sociétés coopératives - Goudem, Jules (Revue générale de droit, 2015)
La création des coopératives en Afrique remonte à la période coloniale. Elles sont aujourd’hui régies par l’Acte uniforme du 15 décembre 2010 relatif au droit des sociétés coopératives. S’affranchissant de la tutelle administrative vers 1990, elles sont devenues démocratiques et évoluent doucement vers les sociétés commerciales, mais différemment des entreprises individuelles et sociétés par actions. Comme l’Acte uniforme qui les régit permet à toute personne, quelle que soit sa nationalité, d’exercer en société coopérative une activité dans l’espace de l’OHADA et que l’article 296 de l’Acte définit le statut du représentant permanent de la personne morale coopératrice, des étrangers, dont les Occidentaux, peuvent y exercer cette activité. Fort de la susdite dynamique, les sociétés coopératives peuvent, au regard du droit canadien, offrir tous les types de produits ou de services et accomplir des actes de commerce. Au sein de ces différents droits, lesdites sociétés sont largement réfractaires à la nullité. Dès lors, il se pose un problème relatif à l’étendue de leur nullité et de celle de leurs actes. Cette analyse répond à la question en montrant que le domaine des nullités est aujourd’hui restreint, de façon assez ambiguë, par l’Acte uniforme et la pratique qui favorise la régularisation de certains actes nuls en matière de société coopérative.
Keywords: Cause immorale; Consent; Consentement; Cooperative; Development; Développement; Immoral cause; Interpretation; Interprétation; Nullity; Nullité; Regulation; Régularisation; Sociétés coopératives

Efficacité des mécanismes de gouvernance des PME : une évaluation empirique en contexte camerounais - Moungou Mbenda, Sabine Patricia; Niyonsaba Sebigunda, Edson (Revue internationale P.M.E., 2015)
Cet article teste l’hypothèse de la gouvernance comme facteur de performance des PME via une analyse multidimensionnelle. Des données d’enquête auprès de 300 PME camerounaises permettent de construire un indice de qualité de gouvernance (IQG) avec 39 variables des mécanismes de gouvernance spécifiques aux PME. Au moyen des modèles économétriques, l’IQG est confronté à trois indicateurs de la performance : le chiffre d’affaires, la création d’emplois et la pérennité. Les résultats révèlent un IQG moyen égal à 0,473 avec un écart-type de 0,231, sur une échelle allant de 0 à 1. Par ailleurs, il existe une relation positive et significative entre l’IQG et les indicateurs de performance retenus, ce qui montre que les pratiques de gouvernance déployées au sein des PME améliorent leur performance. En effet, une amélioration unitaire dans l’IQG induit une augmentation plus proportionnelle du chiffre d’affaires de la PME. De même, la probabilité moyenne prédite pour qu’une PME crée des emplois est majorée de 24,76 %, suite à une amélioration unitaire de l’IQG. Enfin, la variation unitaire de l’IQG rallonge de 3 ans l’âge moyen des PME de l’échantillon qui est de 8,5 ans. This article tests the hypothesis of governance as a performance factor of SMEs by means of a multidimensional analysis. Data obtained from a survey of 300 cameroonian SMEs enabled the structuring of a Governance Quality Index (GQI) with 39 SMEs-specific governance mechanism variables. Making use of econometric models, the GQI is tallied against three performance indicators : turnover, job creation, and sustainability. Results reveal a mean GQI of 0,473 with a standard deviation of 0,231 on a scale of 0 to 1. Moreover, there is a positive and significant link between GQI and the performance indicators, which shows that governance practices implemented within SMEs improve their performance. In effect, a unit improvement in the GQI triggers a more proportionate increase in the turnover of the SME. Likewise, the mean probability of a SME creating jobs is increased by 24,76 % following a unit improvement of the GQI. Finally, the mean age of 8,5 in our simple is extended by 3 years further to the unit variation of the GQI. Este artículo testa la hipótesis de la gobernación como factor de resultado de las PyMEs vía un análisis multidimensional. Datos de encuesta cerca de 300 camerunesas permiten construir un Índice de Cualidad de Gobernación (ICG) con 39 variables de los mecanismos de gobernación específicos a las PyMEs. Por modelos econométricos, el ICG se enfrenta con tres indicadores de resultado : el volumen de negocias, la creación de empleos y perennidad. Los resultados revelan un ICG medio equivalente a 0,473 con una raíz cuadrada de variación de 0,231 ; sobre una escala de 0 hasta 1. Por otra parte, existe una relación positiva y significativa entre el ICG y los indicadores de resultado seleccionado, lo que muestra que las prácticas de gobernación desplegadas dentro de las PyMEs mejoran su resultado. En efecto, un mejoramiento unitario en el ICG induce un aumento más proporcional del volumen de negocios de la PyME. Asimismo, la probabilidad media predicha para que una PyME cree empleos está sobrestimada de 24,76 % después de un mejoramiento unitario del ICG. Finalmente, la variación unitaria del ICG alarga de 3 años la edad media de los PyMEs de la muestra que es de 8,5 años.
Keywords: Gobernación; Gouvernance; Governance; Governance quality index (GQI); Indice de qualité de gouvernance (IQG); PME; Performance; PyMEs; Resultado; SMEs; Índice de cualidad de gobernación (ICG)

Building legal bridges: fostering eastern Africa integration through commercial arbitration - Muigua, David K. (Alternative Dispute Resolution, 2015)
This paper explores the feasibility of commercial arbitration as a means to foster the process of Eastern Africa integration. The author proffers an argument in the context of Eastern Africa integration, that commercial arbitration offers a better platform for dealing with commercial disputes that are bound to arise considering the differing personal or state interests in the ongoing Eastern Africa integration, as compared to national Courts. This discourse is premised on the fact that the five member countries making up the East African Community (EAC) have different legal systems and this presents a major challenge in harmonising the various legal systems. This also affects the possible use of courts in managing the potential transnational commercial disputes due to the potentially different rules of procedure and practice. The paper briefly examines the state of commercial arbitration in the EAC Member States with a view to identifying the existing frameworks and any impediments in their effectiveness. Finally, the author makes a case for utilizing commercial arbitration to build bridges and foster Eastern Africa integration for development.
http://erepository.uonbi.ac.ke/handle/11295/81712
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

L’intérêt des parties dans l’abus d’exercice des voies de droit - Ndiaye, Ndèye (Revue générale de droit, 2015)
L’exercice d’une voie de droit oppose une partie en droit d’exiger le respect de sa prérogative et une autre devant répondre de son obligation. Alors, les intérêts en présence sont naturellement divergents, car chaque partie oeuvrera pour sortir triomphante du conflit. Ainsi, le risque d’en arriver à un abus est réel, et c’est ce qui justifie la sanction. Il ne faudrait pas que par l’exercice d’un droit, un justiciable soit lésé. Ses intérêts sont ainsi protégés par la modération de l’exécution des droits des uns et des autres. Par ailleurs, il ne faudrait pas, non plus, porter atteinte à l’intérêt des parties par un encadrement trop élastique de la notion d’abus. En effet, la sanction de l’exercice abusif d’une voie de droit peut dissuader les plaideurs. Ce serait, ainsi, violenter l’accès au droit, qui est fondamental dans la réalisation des droits subjectifs. La consécration de la loyauté permettrait d’éviter ces dérives.
Keywords: ABUS; Abuse; Action; Caractérisation; Criteria; Execution; Exécution; Interest; Intérêts; Remedy; Voie de droit

Quelques réflexions sur le silence et le droit : essai de systématisation - Ngah Noah, Marcel Urbain (Les Cahiers de droit, 2015)
Le silence côtoie indiscutablement le droit. Il s’agit d’un couple en interaction. Le silence saisit le droit à travers les silences du droit. Ces silences, justifiés par plusieurs raisons, sont protéiformes et source d’incertitude. Le droit essaie tant bien que mal de les combler quand il ne les génère pas lui-même. Par ailleurs, le droit appréhende le silence en tentant de le juridiciser. Entreprise perceptible à travers non seulement le droit au silence, mais aussi par l’imposition ou l’interdiction du silence selon les cas. Constatant la présence du silence, le droit l’interprète en lui octroyant ou non une portée juridique.

L’égalité des créanciers dans les procédures collectives internationales : Étude comparative du droit OHADA et européen - Ngono Nkoa, Carole-Véronique (Revue internationale de droit comparé, 2015)
L’égalité des créanciers n’est pas un mythe ! Elle est bien présente dans les procédures collectives internationales OHADA et européenne. Cependant, et en dépit de l’uniformisation des procédures, l’OHADA, qui s’est inspiré du droit communautaire européen n’a pas pu endiguer les obstacles liés à la mise en oeuvre de ce principe dans les procédures collectives internationales. Ces obstacles bien que différents selon les espaces ont un point commun, celui de rendre plus difficile l’appréhension des actifs du débiteur situés en dehors de l’État d’ouverture de la procédure. Mais les solutions à ce problème peuvent plus facilement s’adapter à l’OHADA compte tenu de l’unicité du droit applicable dans l’espace OHADA.

Challenges of Transnational Trademark Law Practice: The Case of Nigerian Companies’ Brands in OAPI States - Nwabueze, Caroline (Revue générale de droit, 2015)
Nigeria industrial growth has turned the country into an indispensable economic support for its neighbours. Only for the case of Cameroon, Nigeria has been the leading supplier with respectively 22% and 17.8% of imports in 2011 and 2012 with trade amounting to 328 billion FCFA per annum. This results in part from Nigerian companies’ exportations in local markets. Nigerian trademarks related to cosmetics, furniture, electronics, and pharmaceutical goods abound in neighbouring countries. However, a strengthening of Nigerian companies in regional markets encompasses strategies to avoid infringing on the trademark rights. Such strategies should include the consideration of special trademarks features by different institutions of the intellectual property (IP) system in the relevant neighbour export markets. This is by the mere fact that the legal status of those goods, although physical property, relies mainly on the material law applicable, which is trademark in the present case. Because the principle of territoriality requires that trademark protection be sought in the place where the goods are sold—and trademark applications filed in each country in which protection is sought—, Nigerian companies planning to outsource some business activity in neighbour markets will seek compliance with trademarks norms applicable in the Organisation africaine de la propriété intellectuelle (OAPI) of which those countries—Benin, Cameroon, Chad, and Guinea—are part. The trade partnership between companies from a common law trademark background on one hand, and civil law intellectual property community on the other, inevitably raises some frictions and trademarks issues. This article analyses the trademark challenges arising from Nigerian companies’ business decision to enter OAPI markets and export goods and services. The article firstly underlines the issues to be taken into consideration, including registration and enforcement of the companies’ marks in OAPI. Then the paper simultaneously reviews the dissimilarities issues between the Nigerian Trademark Act and the OAPI Trademark System to which the Nigerian companies are confronted. If trademark protection makes it easier for an enterprise to access transnational markets, the establishment of a Trademark Community with neighbouring countries helps for sure national industries to establish partnerships with other firms for sustainable development in the areas such as production, marketing, distribution or delivery of goods and services. In light of the trademark harmonisation in the European Union internal market, the present paper concludes by recommending the creation of a Trademark Community in the West and Central African region between Nigeria and its neighbouring countries. La croissance industrielle du Nigeria a fait de ce pays un soutien économique indispensable pour ses voisins. Pour ne citer que l’exemple du Cameroun, le Nigeria en a été le principal fournisseur avec respectivement 22 % et 17,8 % des importations en 2011 et 2012 et des importations dont la valeur s’élève à 328 milliards fr. cfa par année. Ceci résulte en partie des exportations des compagnies nigérianes vers les marchés locaux. Les marques de commerce nigérianes dans le domaine des cosmétiques, des meubles et des produits électroniques et pharmaceutiques abondent dans les pays voisins. Cependant, le renforcement des compagnies nigérianes dans les marchés régionaux englobe des stratégies pour éviter d’enfreindre les droits de propriété industrielle et commerciale. Dans le cadre de ces stratégies, les différentes institutions qui régissent la propriété intellectuelle (PI) dans les marchés d’exportation des pays voisins pertinents devraient prendre en compte des caractéristiques particulières relatives aux marques de commerce. Ne serait-ce que du simple fait que le statut juridique de ces produits, bien qu’ils soient des biens physiques, repose principalement sur le droit substantiel applicable, le droit de la marque de commerce dans ce cas. Parce que le principe de territorialité nécessite que la protection de la marque de commerce soit demandée dans le territoire où les biens sont vendus, et que cette protection doit être demandée dans chaque pays individuellement, les compagnies nigérianes qui prévoient externaliser des activités commerciales dans des marchés voisins chercheront à se conformer aux normes en matière de marques de commerce qui sont applicables au sein de l’Organisation africaine de la propriété intellectuelle (OAPI), dont font partie le Bénin, le Cameroun, le Tchad et la Guinée. Le partenariat commercial entre des entreprises soulève inévitablement, et ce, tant du point de vue de la common law que celui du droit civil, des frictions et des problèmes lorsqu’il s’agit de marques de commerce. Le présent article analyse les défis relatifs aux marques de commerce découlant de la décision commerciale des entreprises nigérianes de faire leur entrée dans les marchés de l’OAPI et d’y exporter des biens et services. L’article souligne premièrement les problèmes qui doivent être pris en considération, dont l’inscription et la mise en application des marques des entreprises membres de l’OAPI. Ensuite, ce texte examine simultanément les problèmes résultant des différences entre la Nigerian Trademark Act et le système de marques de commerce de l’OAPI, système auquel les entreprises nigérianes sont confrontées. Si la protection des marques de commerce facilite l’accès aux marchés transnationaux pour les entreprises, la mise en place, avec les pays voisins, d’une communauté en matière de marques de commerce aide assurément les industries nationales à établir des partenariats avec d’autres entreprises dans le but d’assurer un développement durable dans des domaines tels que la production, la commercialisation, la distribution ou la livraison de biens et services. À la lumière de l’harmonisation des marques de commerce dans le marché intérieur de l’Union européenne, le présent article conclut en recommandant la création d’une communauté de marques de commerce dans la région de l’Afrique occidentale et centrale, et qui réunirait le Nigeria et ses pays voisins.
Keywords: Afrique occidentale; Commerce transnational; Communauté de marques de commerce; Community trademark; Compagnies nigérianes; Enforcement; Intellectual property; Marque déposée; Mise en oeuvre; Nigerian companies; OAPI; Principe de territorialité; Principle of territoriality; Propriedade intelectual; Propriété intellectuelle; Trademark practice; Transnational trade; Western Africa

Corporate Social Responsibility , Oil Exploration and the Niger Delta Question - Obi, Emeka Anthony (Oman Chapter of Arabian Journal of Business and Management Review, 2015)
The intricate relationship between corporate organizations and their environment is one that is supposed to be based on mutual interdependence. This is because the organization depends on the environment for its inputs, while the environment also needs the organization for its sustenance. This therefore calls for a symbiotic relationship between them. It is this realization that gave birth to the concept of Corporate Social Responsibility (CSR). This paper tries to look at the application of the concept as it concerns the oil companies operating in the Niger Delta region of Nigeria within the ambit of the Niger Delta question. The study employs the systems theory as an analytical framework. It tries to situate the concept of CSR within the general neglect by successive governments of this region that sustains the entire Nigerian state. The implication of the above is that a better understanding of the problem of CSR in the Niger Delta region becomes easier when juxtaposed with the attitude of the Nigerian state towards the region over the years. It is the summation of the paper that the oil companies have not been very proactive in this regard and as such have been perceived by their host communities as enemies and exploiters instead of partners. The study concludes by insisting that while the oil companies should be more proactive, the government on her part should step up the tempo in ameliorating the deplorable condition of the golden goose.
Keywords: CSR; Corporate Social Responsibility; RSE; Responsabilité Sociale de l'Entreprise

Stuck in a time warp: security interests in chattel mortgages and the bills of sale legislation in Nigeria - Otabor-Olubor, Iyare (International Company and Commercial Law Review, 2015)
IRep - Nottingham Trent University's open access institutional research repository
Number: 11

Partir du droit pour aborder le problème de l’économie informelle : réflexions sur le projet d’une norme internationale à travers deux « économies informelles » au Togo - Panier, Élise (Sociologie et sociétés, 2015)
En partant du récent projet de norme de l’OIT visant à favoriser la formalisation de l’économie informelle, cet article propose d’interroger la démarche institutionnelle à travers une réflexion sur le droit comme critère d’intelligibilité de la catégorie de l’informel. Sur la base d’une enquête réalisée au Togo, cette contribution présente les modalités nombreuses et complexes des manifestations du droit du travail et du droit de l’activité économique dans les deux espaces d’informalité du travail que sont la zone franche d’exportation et le secteur dénommé informel au Togo. Entre surformalisation spécifique et im-pénétration publique ou syndicale dans un cas, et intervention publique et syndicale relativement quotidienne dans l’autre, la manière de vouloir faire de l’économie informelle un objet d’intervention global, en distinguant l’emploi informel des unités économiques, n’est pas sans soulever des questions sur la pertinence de la démarche et le rôle de ce concept souvent critiqué mais, paradoxalement, d’usage permanent.
Keywords: Derecho trabajo; Droit du travail; Economie informelle; Free export zone; Informal economy; Labour law; Rights; Togo; Zona franca exportación; zone franche d’exportation

CISG and the freedom of form principle vs. reservations under Article 96 of the CISG - Pohl, Małgorzata (Transformacje Prawa Prywatnego, 2015)
This article aims to present the consequences of a state’s declaration to opt-out from the freedom of form principle, under article 96 of the united nations Convention on Con tracts for the international sale of goods 1980 (CISG). In practice, problems have developed as whether or not to apply the freedom of form when a contract is concluded between two business entities, where one has its place of business in an article 96 CISG reservation state, and the other does not. The issue concerning the reservation’s effects has led to the creation of “two schools of thought” established by the doctrine and case law in this respect. it is the author’s intention to present the proper methodology of the interpretation and application of articles 12 and 96 CISG bearing in mind the various opinions in this respect. In the author’s opinion, in such situations the court should follow the rules of private international law to seek an answer as to whether or not the obligation of written form applies. Some of the CISG Contracting states that currently maintain an article 96 Cisg dec laration, refrain from withdrawal of their declaration despite the fact that the prerequisites for such a reservation are no longer met, as their domestic legal systems do not impose a written form requirement, as was the case at the time when the Cisg was negotiated. In the author’s opinion, in cases where the rules of private international law point to the law of such a state, the courts should, in practice, refrain from following the article 96 Cisg reservation, i.e. no freedom of form, and should instead apply the less formal domestic law as to the form.

More than 25 years of the contracts for the international sale of goods (CISG): Rethinking the role of the CISG in the SADC region - Shumba, Tapiwa (Speculum Juris, 2015)
The Convention on Contracts for the International Sale of Goods (CISG) has proved popular, particularly outside Africa. However, only a few States have adopted it in Africa, with only two in the Southern African Development Community (SADC). Taking into account the role that African countries have played in the United Nations Commission on International Trade Law (UNCITRAL) and the creation of the CISG, it has always been pertinent to look at whether SADC Member States should adopt the CISG as an instrument for harmonising the law of international sales in the region. Since it came into force, only two SADC Member States (Lesotho and Zambia) have ratified the convention. There is apparent reluctance from the rest of SADC Member States to ratify the convention despite calls to that effect and the genuine need for legal harmonisation. The article revisits the call for the ratification of the CISG in SADC and considers other realistic alternatives to ratification.

Réflexion sur l'adaptation du droit des contrats au numérique - Sow, Djibril (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2015)
La réflexion sur l'adaptation du droit des contrats au numérique révèle la présence du numérique à travers plusieurs règles. Certaines conditions de validité du contrat, tout comme certaines règles générales relatives à l'exécution des contrats sont concernées par l'adaptation au numérique. Cette adaptation vise aussi certaines règles spéciales du droit des contrats. L'Avant-projet de loi sur les transactions électroniques au Mali envisage d'importantes mesures allant, en particulier, dans le sens de l'adaptation du droit des contrats au numérique, un domaine qui continue d'attirer l'attention. The reflection on the adaptation of contract law to the digital reveals the presence of the digital through several rules. Certain conditions of validity of the contract, and some general rules on contract enforcement are involved in the digital adaptation. This adaptation also concerns some special rules of contract law. The proposed draft law on electronic transactions in Mali is planning major steps up, especially in the sense of adaptation of contract law in the digital domain, an area that continues to attract attention
Keywords: Contrat; Règles générales; Règles spéciales; Transactions électroniques

L’accès durable des paysans à la terre : quel peut être l’apport des coopératives à la lutte contre l'accaparement des terres en Afrique ? - Tadjudje, Willy (Revue des mutations en Afrique : Réflexions sur les politiques et les pratiques, 2015)
Depuis plusieurs années, on remarque une ruée sur les terres cultivables en Afrique. Ce déferlement peut s’expliquer par diverses raisons, telles que la recherche de nouvelles rentabilités à la suite de la crise financière actuelle, l’accroissement de l’investissement agricole pour assurer la sécurité alimentaire, l’encouragement de l’agrocarburant, etc. Toutefois, le phénomène n’est pas sans conséquence sur le bien-être des paysans locaux. Ces derniers, généralement réunis autour de sociétés coopératives, peuvent défendre leurs intérêts à travers diverses formes d’actions. À cet effet, le mouvement coopératif peut jouer un rôle important dans la lutte contre le phénomène de l’accaparement des terres en Afrique. For several years, an important rush for farmland is noticeable in Africa. This surge can be explained by various reasons, such as the search for new profits as a result of the current financial crisis, the increasing of investment in agriculture to ensure food security, the promotion of agro-fuel etc. However, the phenomenon is not without consequences for the well-being of local farmers. These latter, usually gathered around cooperative societies, can defend their interests through various forms of action. To this end, the cooperative movement can play an important role in the fight against the phenomenon of land grabbing in Africa.

Le commissaire aux comptes et le ministère public en droit OHADA des sociétés commerciales - Taita, Taita (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2015)

La chose jugée et la vérité dans le procès civil en droit camerounais - Tjouen, Alex-François (Revue internationale de droit comparé, 2015)
Le juriste a coutume de dire que lorsque la chose est jugée, la vérité est dite. Le juge doit néanmoins crédibiliser sa décision en usant des moyens de droit mis à sa disposition non seulement pour objectivement révéler cette vérité, mais aussi pour imposer l’exécution de la décision rendue. Encore faudrait-il cependant distinguer selon que cette vérité est provisoire ou définitive. Le premier cas concerne la décision ayant acquis une simple autorité de chose jugée. Il suffit alors d’exercer la voie de recours appropriée pour que la décision soit contestée et son exécution éventuellement suspendue. Désormais, ce qui tenait lieu de vérité est mis entre parenthèse. La vérité est plutôt définitive dans le cas où, au-delà d’une simple autorité, la chose jugée a acquis une véritable force. Si cette affirmation ne peut être contestée, elle doit cependant être nuancée dans la mesure où même une décision investie de la force de chose jugée peut encore être remise en cause. Finalement, la décision du juge est une vérité judiciaire qui, pourquoi pas, est peut-être loin d’être la vérité. The legal person usually says that when a thing is judged, the truth is said. The judge should nevertheless give credibility to his decision using the law tools put at his disposal, not only to objectively reveal this truth, but also to enforce the implementation of the decision. But it should be necessary however to distinguish if this truth is temporary or final. The first case concerns a decision which has acquired the single authority of res judicata. Simply applying the appropriate way of appeal can cause that decision to be challenged and possibly suspended. Henceforth, what was truth is put in brackets. The truth is rather final where, beyond a single authority, res judicata has acquired a real force. If this assertion cannot be challenged, it must however be qualified insofar as even a decision appointing the force of res judicata may still be questioned. Finally, the decision of the judge is a judicial truth which, why not, is perhaps far from the truth.

A Standing Question: Mortgages, Assignment, and Foreclosure - Zacks, Eric A; Zacks, Dustin A (The Journal of Corporation Law, 2015)
“Banks are neither private attorneys general nor bounty hunters, armed with a roving commission to seek out defaulting homeowners and take away their homes in satisfaction of some other bank’s deed of trust.” This Article examines the judicial treatment of mortgage assignments across various jurisdictions in the foreclosure context. Although some courts do permit debtors to challenge suspicious or problematic assignments, most have ignored such problems and denied standing to debtors attempting to assert assignment-based defenses. This is particularly surprising given the widespread and well-documented problems with foreclosure “robo-litigation,” including backdated documents, fraudulent notarizations, and unauthorized signatures. Despite the abuse of process by foreclosing entities, courts have permitted foreclosures to continue unabated and, in some instances, have even precluded the possibility of discovery to debtors seeking to ensure that title and assignments are legally valid. Judicial ambivalence about formal compliance by mortgage assignors and assignees in the foreclosure context is somewhat ironic given most courts’ routine enforcement of instruments against debtors who do not formally comply with all contractual terms. Current adjudicative approaches to mortgage assignment are seemingly disconnected from the devastating reality of the home mortgage crisis and its causes. Moreover, there are several rationales that would support a more robust enforcement of technical compliance with assignment procedures, including the need for procedural equity, title certainty, and public records integrity. Thus, as evidence exists that banks are still making many of the same problematic mistakes regarding transfer documentation, courts can perform an essential monitoring role as an important spur towards reform. Although it would not address all of the underlying causes of the housing crisis, an adjudicative approach that liberally permits challenges to mortgage assignments would encourage lenders and servicers to be more circumspect in their foreclosure processes.